Core competencies of nurses in palliative care in the intensive care unit: A literature review - Yosi Rianti; Nurul Huda; Erika Erika (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Palliative care is a healthcare approach that aims to improve the quality of life of patients with life-threatening illnesses through symptom management, psychosocial and spiritual support, and effective communication. The need for palliative care in the Intensive Care Unit (ICU) continues to increase alongside the growing complexity of critically ill patients. Nurses, as frontline healthcare providers, play a crucial role in implementing palliative care and therefore require comprehensive and standardized core competencies. Purpose: To examine research findings related to core competencies in palliative care among ICU nurses and to identify the factors influencing these competencies in clinical practice. Method: This study employed a literature review design using a narrative synthesis approach. Literature searching were conducted in PubMed, Scopus, ScienceDirect, SAGE, and Google Scholar for articles published between 2020 and 2025. Among the 312 articles identified, eight studies met the inclusion criteria and were analyzed in depth. Results: The findings indicate that core competencies in palliative care among nurses consistently encompass several key domains, including clinical symptom management, therapeutic communication, team collaboration, ethical and legal aspects, psychosocial and spiritual support, and self-reflection and professionalism. However, the level of nurses’ competencies, particularly in the ICU, remains predominantly in the low to moderate categories. Various factors influencing competency include work experience, level of education, self-directed learning ability, attitudes toward death, and moral distress. In addition, studies have revealed that palliative care education and training remain suboptimal, which contributes to variations in practice and quality of care. Conclusion: Palliative care competencies among ICU nurses still require strengthening, particularly through structured education, competency-based training, and the integration of palliative care into clinical practice. Strengthening educational systems and organizational support is essential for improving the quality of palliative care services in the ICU.